Experiences of Internally Displaced Persons (IDPs) in Dikwa, Borno State, Nigeria, 2014-2020 - Alhaji Modu, Ibrahim; Samaila Maina, Yakubu (Kashere Journal of Humanities, Management and Social Sciences, 2022)
The activities of Boko Haram insurgents in Kanama area of Yobe State started in 1995, and by 2009, had successfully engulfed all the Local Government areas of Borno, Yobe and a number of States in Northern Nigeria. Dikwa, one of the twenty-seven (27) Local Government Areas of Borno State, had tasted the bitter pills of the insurgency. The insurgents inflected a colossal loss of lives and properties amounting to millions of naira in the area. The paper attempts to present the genesis, development and spread of the activities of Boko Haram insurgents in Dikwa, Borno State. The nature and operation of the insurgents as well as consequence on the people of Dikwa living in the town and the displaced population of the area, presently camped in Shehu Sanda Kyarimi II camp in Maiduguri, the Borno State capital. The paper also examines the conditions of internally displaced persons in the camp as well as the aftermaths of the insurgency in Dikwa and the conclusion attempts to draw out some results of the study. The study relied heavily on oral interviews with camp official as well as the actual victims of the insurgency and secondary sources. Lee Everet ‘s push and pull factor theory of migration and Maslow’s theory of needs were used and served as the conceptual framework in this study.